Seychelles : Fourth Review Under the Extended Arrangement, Request for Waiver of Applicability of Performance Criteria and Financing Assurance Review: Staff Report; Press Release on the Executive Board Discussion; Statement by the Executive Director for Seychelles. (IMF Staff Country Reports; Country Report ;, 2012)
Seychelles's fiscal stance for 2012 allows maintaining a steady course toward debt reduction. The authorities' decisions to downsize the loss-making national airline and raise tariffs of public enterprises are crucial steps for easing fiscal pressures and ensuring sufficient capital expenditure, in particular in much-needed infrastructure projects. Price subsidies through the Stabilization Fund will be replaced with targeted transfers to low-income households. The structural reform agenda for 2012 builds on progress made to date, focusing on taxation, public finance management, public enterprises, and the financial sector.